2011
DOI: 10.2166/9781780400778
|View full text |Cite
|
Sign up to set email alerts
|

Bioanalytical Tools in Water Quality Assessment

Abstract: Bioanalytical Tools in Water Quality Assessment reviews the application of bioanalytical tools to the assessment of water quality including surveillance monitoring. The types of water included range from wastewater to drinking water, including recycled water, as well as treatment processes and advanced water treatment. Bioanalytical Tools in Water Quality Assessment not only demonstrates applications but also fills in the background knowledge in toxicology/ecotoxicology needed to appreciate these applications.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 0 publications
1
51
0
1
Order By: Relevance
“…Thus, compounds that are analytically not detected, e.g. transformation products, and mixture effects are challenges where it is suggested that employing bioanalytical tools will improve assessments (Escher et al, 2011). A variety of effect-based tools will therefore be advanced to various degrees of applicability.…”
Section: Tools and Models For The Identification Of Hazardous Substanmentioning
confidence: 99%
“…Thus, compounds that are analytically not detected, e.g. transformation products, and mixture effects are challenges where it is suggested that employing bioanalytical tools will improve assessments (Escher et al, 2011). A variety of effect-based tools will therefore be advanced to various degrees of applicability.…”
Section: Tools and Models For The Identification Of Hazardous Substanmentioning
confidence: 99%
“…Healthbased guidelines are also available for recycled water for indirect potable reuse and for various other water types and environmental protection goals (Escher and Leusch, 2012). Snyder et al (2008) proposed to derive drinking water equivalent levels for pharmaceuticals using the minimum therapeutic dose.…”
Section: Chemical Water Quality Guidelines To Protect Human Healthmentioning
confidence: 99%
“…Lower concentrations of analyte (in this case, referring to Hg 2+ ) were not bioavailable to the detection chain after loss by adsorption, evaporation, precipitation, or complexation (van der Meer et al, 2004). However, the total lux luciferase activity decreased because higher doses of the analyte became cytotoxic and destroyed the host cells (Escher and Leusch, 2012). In this research, the recombinant train showed no luminescence activity when exposed to 10 μmol/L or higher doses of Hg 2+ .…”
Section: Sensitivity and Specificity Of Pthe30-e Colimentioning
confidence: 72%